Indexicality of Minyak Karo in North Sumatra: An Anthropolinguistic Perspective - Tarigan, Karisma Erikson; Lubis, Tasnim (TALENTA Publisher, 2022)
This study aimed to describe the indexicality Minyak Karo in North Sumatera. It focused on describing the ingredients used for making the Minyak Karo, the ritual process of making Minyak Karo, the purpose of the ritual carried out in making Minyak Karo, and performance in the ritual of making Minyak Karo in Padang bulan and Pancur batu regency, North Sumatra. Qualitative method and Anthropolistic perspective were applied in this study. The data collection techniques used was observation, in-depth interviews and documentation. The result of the study showed that there were 107 genera and 57 families in making Minyak Karo to treat different diseases, such as kaffir lime/kaffir lime leaves, ship-board leaves, jambar api, bulung patchouli, gagaten tiger, basil, panglai, shallots, garlic, pepper, nutmeg, turmeric, areca nut, tawan gegeh, root areca nut, bamboo root, riman root, pengkih root, and alang-alang. The purpose of the ritual of making Minyak Karo based on anthropolingustic study was to be able to cure diseases that were believed to come from supernatural spirits or diseases sent by people through supernatural means and asked for protection from the spirits of the ancestors.